The results of using micropulse cyclophotocoagulation for the treatment of patients with primary open-angle glaucoma - V.V. Egorov; A.V. Postupaev; N.V. Postupaeva (РМЖ "Клиническая офтальмология")
V.V. Egorov1,2, A.V. Postupaev1, N.V. Postupaeva1 1Khabarovsk Branch of the S. Fedorov Eye Microsurgery Federal State Institution, Khabarovsk, Russian Federation 2Institute of Advanced Training of Healthcare Specialists, Khabarovsk, Russian Federation Aim: to evaluate the clinical efficacy and safety of using micropulse cyclophotocoagulation (MP-CPC) for the treatment patients with mild and moderate stages of primary open-angle glaucoma (POAG). Patients and Methods: the clinical study included 56 patients (62 eyes) with POAG, 49–82 years old. The mild stage of glaucoma was detected in 33 eyes and the moderate stage — in 29 eyes. The level of intraocular pressure (IOP) before surgery ranged from 25 to 38 mm Hg (mean 29.2±2.8 mm Hg). All patients underwent MP-CPC according to the standard technique with the use of the Cyclo G6 Glaucoma Laser System and the MicroPulse P3 probe (IRIDEX, USA). The follow-up period was 6 months. Results: no complications were reported after the surgeries. The mean level of intraocular pressure at day 1 after surgery was 21.7±1.9 mm Hg. A gradual intraocular pressure decrease was recorded by the third week after the surgical treatment, and its stabilization to 17.9±1.9 mm Hg occurred by the sixth month of observation in 94% of the eyes. At day 1 after the surgery, the reduction of intraocular pressure was more pronounced in patients with dark (brown) color of the iris in comparison with patients who had light (blue) color of the iris. It was found that up to 6 months after the surgery, the group of patients under 60 years of age had a more noticeable postoperative hypotensive effect when compared to the patient group over 71 years. Conclusion: MP-CPC was an effective and safe operation for normalizing intraocular pressure in most of the patients with mild to moderate stages of POAG during the 6-month follow-up period. Considering the minimization of the surgical trauma, MP-CPC can prolong the hypotensive effect and preserve visual functions in patients with mild to moderate stages of glaucoma in the near-term future (up to 6 months) after the surgical treatment. Keywords: micropulse cyclophotocoagulation, primary open-angle glaucoma, mild stage, moderate stage, intraocular pressure. For citation: Egorov V.V., Postupaev A.V., Postupaeva N.V. The results of using micropulse cyclophotocoagulation for the treatment of patients with primary open-angle glaucoma. Russian Journal of Clinical Ophthalmology. 2022;22(4):204–209 (in Russ.). DOI: 10.32364/2311-7729-2022-22-4-204-209.